Binding and bridging social capital in the cooperation of tourism sector entrepreneurs - Czernek-Marszałek, Katarzyna (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
In inter-organizational relations, in particular in cooperation, social capital plays a key role. This is both so-called bonding capital – based on closer relationships with entities belonging to one social group and bridging capital – built between entities belonging to different groups. The purpose aim of the chapter is to present the importance of both types of social capital – bonding and bridging – and the relationship between them for undertaking and developing inter-organizational cooperation in the tourism sector. The research carried out with tourist entrepreneurs was used. It was found that in the cooperation of tourism enterprises, the use of both types of capital is needed and they are complementary to each other. The right relations (proportions) between them are also important and they change depending on the conditions of cooperation.